2018
DOI: 10.5039/agraria.v13i3a5545
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution pattern of Euxylophora paraensis Huber in a natural managed forest in the Eastern Amazon

Abstract: The objective of this work was to characterize the spatial distribution pattern of the Euxylophora paraensis (yellowwood), to support conservation strategies of this species population in a managed 'terra firme' forest in the state of Pará. The study area is located in Fazenda Rio Capim, which belongs to The CKBV Florestal Ltda., in the municipality of Paragominas. For analyzing the spatial distribution of trees, geostatistics was used, based on the semivariogram modeling and kriging mapping. All evaluations h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The authors highlighted that, for the forest species analyzed, the best fits were obtained with the Spherical model. Brandão et al (2018), when studying the spatial distribution of Euxylophora paraensis Huber in natural forest managed in the Eastern Amazon, also reported that the best fit was obtained with the Spherical model. This occurs because the semivariogram of each forest species analyzed needs to be fitted with best model.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The authors highlighted that, for the forest species analyzed, the best fits were obtained with the Spherical model. Brandão et al (2018), when studying the spatial distribution of Euxylophora paraensis Huber in natural forest managed in the Eastern Amazon, also reported that the best fit was obtained with the Spherical model. This occurs because the semivariogram of each forest species analyzed needs to be fitted with best model.…”
Section: Discussionmentioning
confidence: 91%
“…Estimates are generated from the information about sample position and the value of the variable at each point. Thus, the value of the variable and the coordinates (x and y) are obtained for each sampling point and used to construct the maps of distribution of forest species (BRANDÃO et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Gaps created in the forest canopy favor height growth but later, this growth decreases due to canopy closure by the lateral crown´s expansion. E. paraensis occupies the upper stratum requiring full sunlight to grow (Brandão, et al, 2018).…”
Section: Population Dynamics Of E Paraensismentioning
confidence: 99%
“…Brazilian yellowwood has a long history of use in Pará, where the wood's renowned beauty and structural robustness led to intense harvesting for use as flooring and finishing structures (Freitas, et al, 2019). The substantial exploitation of the species in the 1990s occurred without any planning and drastically reduced its natural populations (Brandão, et al, 2018). Consequently, the intense harvesting associated with restricted distribution and population reduction explained the inclusion of E. paraensis in the list of threatened species.…”
Section: Introductionmentioning
confidence: 99%
“…Next, the spatial dependence index (SDI) was calculated, determined by the ratio (C0 / (C0 + C1)), where SDI <0.25 is considered strong; when SDI is between 0.25 -0.75, it is considered moderate and when SDI> 0.75 it is considered weak (Cambardella et al, 1994;Brandão et al, 2018).…”
Section: Cernementioning
confidence: 99%